Embracing knowledge driven devices: service oriented standardisation of production management in automated lines. (1st January 2013) - Raza, Muhammad Baqar; Kirkham, Tom; Harrison, Robert
For multinational manufacturers the benefit of flexible real-time and distributed computing is yet to be fully embraced. This is because the critical business function of the manufacturer is on the disconnected shop floor. The support needed for an automated production line can be seen in service oriented computing environments. The current research work at Loughborough University into the application of embedded web services at the factory floor are yielding positive results in terms of integration within a distributed computing infrastructure. This is further enhanced with the integration of ontologies representing knowledge of the line being used in web services. This paper describes the development of the service infrastructure to present service enabled production line control, execution, configuration and monitoring.